The experimental design approach to removal of endocrine disrupting compounds from domestic wastewater by electrooxidation process - Sozudogru, Onur; Kocoglu, Elif Seda; Ylmaz, Alper Erdem; Bakirdere, Sezgin; Komesli, Okan Tarik (SPRINGER, 2023)
In this study, the treatment performance of the process in the removal of Endocrine Disrupting Compounds (EDCs) from domestic wastewater by a laboratory-scale electrooxidation process using Ti/IrO2/RuO2 electrodes as an anode was evaluated using the response surface method (RSM). The effect of pH (3.00-9.00), current density (10-20 A), and flow rate (8-16 mL/min) on the electrochemical removal of 17 alpha-ethinylestradiol, beta-estradiol, triclosan, and estrone has been studied. The Box-Behnken Design (BBD) was used to optimize the parameters that affect the removal efficiencies of the Electrooxidation process (EOP), and second-order quadratic models were developed for the EOP process. Under optimum conditions of current density = 10 A, pH = 3.00 and flow rate = 13.93 mL/min, the maximum removal efficiencies of triclosan, 17 alpha-ethinylestradiol and beta-estradiol, and minimum energy consumption are 91.65, 96.43 and 96.65% and 41.606 kWh/m(3), respectively. The Response Surface Method predicted values that reasonably agreed with the experimental values. At the same time, the electrooxidation method is not successful in completely removing estrone from wastewater. [GRAPHICS] .
Keywords: Endocrine-disrupting compounds; Wastewater; Electrooxidation; Response surface method; Optimization; BORON-DOPED DIAMOND; RESPONSE-SURFACE METHODOLOGY; ELECTROCHEMICAL OXIDATION; LANDFILL LEACHATE; DEGRADATION PATHWAY; ANODIC-OXIDATION; PRODUCTS; PHARMACEUTICALS; MINERALIZATION; Electrochemistry